2015
DOI: 10.1118/1.4905376
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time ultrasound‐tagging to track the 2D motion of the common carotid artery wall in vivo

Abstract: The proposed framework enables tagged ultrasound images of in vivo tissues to be acquired in real-time. Such unconventional beamforming strategy contributes to improve tracking accuracy and could potentially benefit to the interpretation and diagnosis of biomedical images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…It is important to note that these methods are not specifically applicable to IVUS, and no intraluminal pressure information was provided; therefore, their tracking errors were obtained from the literature. [18][19][20] The Pearson correlation for our method resulted in P = .999 for subsequent frames in both horizontal and vertical directions and P = .996 and .999 for distant frames in the horizontal and vertical directions. These levels of accuracy were comparable to some state-of-the-art methods 11 present in the literature.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…It is important to note that these methods are not specifically applicable to IVUS, and no intraluminal pressure information was provided; therefore, their tracking errors were obtained from the literature. [18][19][20] The Pearson correlation for our method resulted in P = .999 for subsequent frames in both horizontal and vertical directions and P = .996 and .999 for distant frames in the horizontal and vertical directions. These levels of accuracy were comparable to some state-of-the-art methods 11 present in the literature.…”
Section: Resultsmentioning
confidence: 84%
“…The tracking errors for our proposed method as well as for 8 other methods present in the literature are displayed in Table . It is important to note that these methods are not specifically applicable to IVUS, and no intraluminal pressure information was provided; therefore, their tracking errors were obtained from the literature . The Pearson correlation for our method resulted in P = .999 for subsequent frames in both horizontal and vertical directions and P = .996 and .999 for distant frames in the horizontal and vertical directions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality in industrialized nations. 1 The atherosclerotic process, which causes thickening of the artery wall and reduction of the artery lumen, is the early manifestation of the possible onset of CVDs. 2,3 Studies have shown that the increase in the intima-media thickness (IMT) of the carotid artery is one of the prominent clinical signs of an ongoing atherosclerotic process.…”
Section: Introductionmentioning
confidence: 99%
“…TO schemes are usually combined with phase-based motion estimation techniques [15], [16]. The validation and the feasibility of this method have already been done in conventional imaging [19], [20] and in 3D imaging [21]. This method was also validated in ultrafast imaging [22] where the PWV, and the Young's modulus of the artery phantom were estimate accurately with a mean errors of 2.2%.…”
Section: Introductionmentioning
confidence: 99%